Aerosol backscattering determined from chemical and physical properties and lidar observations over the east coast of Canada - Li, S. M.; Strawbridge, K. B.; Leaitch, W. R.; Macdonald, A. M. (GEOPHYSICAL RESEARCH LETTERS, 1998)
In August to September 1995 a field experiment was conducted over the Gulf of Maine and Bay of Fundy to study the radiative forcing of pollution aerosols. The chemical and physical characteristics of two pollution cases were studied in detail in contrast to a clean atmosphere case. In the pollution cases, NH4++SO4= showed a unimodal distribution with a peak at 0.24 mu m diameter. It was dominant among identified chemical components, including inorganic ions and organic compounds. However, the identified components were only about 1/3 of the aerosol mass as determined from the physical measurements. The unidentified mass, with a large accumulation mode, was likely due to unmeasured organic matter. In the clean case, sea salt was the dominant species with a bimodal distribution. The results were used to calculate the direct backscatter coefficient beta(pi) at 0.532 and 1.064 mu m using the Mie theory for comparison with LIDAR observations to determine the contributions by the chemical components. In the dean case, the sea salt aerosols contributed about half of beta(pi). In the pollution cases, NH4++SO4= contributed 20-40% to beta(pi). The unidentified mass had contributions to beta(pi) of>40% and >70% for the two pollution cases. The LIDAR beta(pi) results were inverted to derive optical depths over the 300-2400 m altitude range. Using these optical depths, the direct backscattered fraction of radiative flux for the pollution aerosols was estimated to be about 5 times higher than aerosols in the clean atmosphere.